Rhodium(I) Pincer Complexes of Nitrous Oxide - Gyton, Matthew R. (Angew Chem Int Ed Engl, 2019)
The synthesis of two well‐defined rhodium(I) complexes of nitrous oxide (N(2)O) is reported. These normally elusive adducts are stable in the solid state and persist in solution at ambient temperature, enabling comprehensive structural interrogation by (15)N NMR and IR spectroscopy, and single‐crystal X‐ray diffraction. These methods evidence coordination of N(2)O through the terminal nitrogen atom in a linear fashion and are supplemented by a computational energy decomposition analysis, which provides further insights into the nature of the Rh–N(2)O interaction.